2019
DOI: 10.1523/jneurosci.3112-18.2019
|View full text |Cite
|
Sign up to set email alerts
|

Visual Feedback Processing of the Limb Involves Two Distinct Phases

Abstract: Muscle responses to mechanical disturbances exhibit two distinct phases: a response starting at ϳ20 ms that is fairly stereotyped, and a response starting at ϳ60 ms modulated by many behavioral contexts including goal-redundancy and environmental obstacles. Muscle responses to disturbances of visual feedback of the hand arise within ϳ90 ms. However, little is known whether these muscle responses are sensitive to behavioral contexts. We had 49 human participants (27 male) execute goal-directed reaches with visu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
52
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(70 citation statements)
references
References 81 publications
(123 reference statements)
2
52
1
Order By: Relevance
“…Besides the potential contribution of muscle afferent feedback, the fact that changes in feedback responses were detected within 250ms leaves enough time to engage task-related feedback responses mediated by touch (Pruszynski et al, 2016;Crevecoeur et al, 2017), and vision, which participates in goal-directed feedback control (Franklin and Wolpert, 2008;Scott, 2016), as well as in rapid changes in navigation strategies (Cross et al, 2019). Characterizing the specific contribution of each sensory system constitutes an exciting challenge for future work.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the potential contribution of muscle afferent feedback, the fact that changes in feedback responses were detected within 250ms leaves enough time to engage task-related feedback responses mediated by touch (Pruszynski et al, 2016;Crevecoeur et al, 2017), and vision, which participates in goal-directed feedback control (Franklin and Wolpert, 2008;Scott, 2016), as well as in rapid changes in navigation strategies (Cross et al, 2019). Characterizing the specific contribution of each sensory system constitutes an exciting challenge for future work.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several studies have suggested that visuomotor feedback is controlled via a pathway through the colliculus (Reynolds and Day (2012); Gu et al (2018); Corneil et al (2004)). Furthermore, it has been suggested that visuomotor feedback responses involve two different phases that are behaviourally different Cross et al (2019). This might reflect two different pathways, the early through the colliculus and the later through cortex.…”
Section: Discussionmentioning
confidence: 99%
“…From intercepting a basketball pass between opponents to catching a vase accidentally knocked off the shelf -visuomotor feedback responses play a familiar role in human motor behaviour. Previous research has extensively analysed these responses in human reaching movements (Day and Lyon (2000); Reichenbach et al (2014); de Brouwer et al (2017de Brouwer et al ( , 2018; Saunders and Knill (2003); Saunders (2004); Saunders and Knill (2005); Sarlegna et al (2003); Knill et al (2011)), and showed an interesting combination of task-dependent variability on the timescale of a single movement (Dimitriou et al (2013); Franklin et al (2014Franklin et al ( , 2017; Cross et al (2019)), as well as sub-voluntary feedback onset times (Prablanc and Martin (1992); Day and Lyon (2000); Franklin and Wolpert (2008); Zhang et al (2018); Oostwoud Wijdenes et al…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the fastest 521 adjustments to state feedback control could be achieved by tuning the long--latency feedback loop. 522 Besides the potential contribution of muscle afferent feedback, the fact that changes in 523 feedback responses were detected within 250ms leaves enough time to engage task--related 524 feedback responses mediated by touch Crevecoeur et al, 2017), and vision, 525 which participates in goal--directed feedback control (Franklin and Wolpert, 2008;Scott, 2016), as 526 well as in rapid changes in navigation strategies (Cross et al, 2019). Characterizing the specific 527 contribution of each sensory system constitutes an exciting challenge for future work.…”
mentioning
confidence: 99%